Rehabilitasi Kolong Pasca Penambangan Timah dengan Teknologi Pertanian Terapung pada Budidaya Tanaman Selada Merah Keriting di Provinsi Bangka Belitung - Syafrullah Syafrullah; Heniyati Hawalid; Minwal Minwal; Neni Marlina (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2018)
Syafrullahet al, 2018. Rehabilitation of Pit after Tin Mining by Floating Agricultural Technology at Red Curly Lettuce Cultivation in the Bangka Belitung Province. JLSO 7(1):88-96. Bangka Belitung Province is the largest tin producer in Indonesia. After tin mining was formed pit/under the surface of the earth . This pit potential was quite large, especially under the colonies near the settlement, in addition to fishery business could also be used with floating plant cultivation. The purpose of this research was to get location-specific cultivation technology of location specific plant at pit after tin mining which was floating plant cultivation technology and utilize the pit after tin mining to be productive pit for cultivation of vegetable crops and preserve the environment by utilizing the pit, plastic waste and grass became useful in the cultivation of floating vegetable crops at the pit after tin mining. This research was conducted from January to May 2016 in Batu Belubang Village, Pangkalan Baru District, Central Bangka Regency of Bangka Belitung Province. The design used was Factor Randomized Random Design (RAK) with 9 treatment combinations repeated 3 times and 5 sample plants. As the indicator plant was red curly lettuce. The treatments were 1) Type of raft (R) with 3 levels,those are R1 = raft of plastic waste size of 250 ml, R2 = raft of plastic waste size of 600 ml, R3 = raft of plastic waste size of 1500 ml and 2) compost type (X) with 3 levels ,namely K1= compost of purun grass K2 = compost of bakung grass and K3 = compost of gegas grass. From the results of the research showed that the type of plastic waste raft size of 250 ml and type of bakung grass compost gave the better growth and production response for curly red lettuce and the application of technology cultivation of curly floating red lettuce plants at the pit after tin mining lead to give the same results and tend to higher if compared with the system of cultivation coventionally on the dry land.